Palinodia sobre la inscripción ibérica del Teatro de Sagunto (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
A wrong information about the dimensions of the Iberian inscription found in the theater of Sagunt led us to an interpretation as a monumental epigraph. In this paper such an interpretation is corrected.